2016
DOI: 10.1186/s12891-015-0859-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rehabilitation approaches for runners with patellofemoral pain: protocol of a randomised clinical trial addressing specific underlying mechanisms

Abstract: BackgroundPatellofemoral pain (PFP) is highly prevalent in runners, and often leads to functional limitations and cessation of running. Training errors as well as decreased lower limb strength and control during running have all been associated with PFP. While strengthening and gait retraining are commonly used by clinicians, no randomised clinical trial has compared these modalities in runners with PFP. The primary objective of this randomised clinical trial will be to compare the effects of three rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Current evidence suggests that increasing cadence can decrease patello-femoral joint stress (Willson et al, 2014) in people with and without PFPS, however a relationship between this and hip muscle activity or biomechanics has not yet been established. Further work is required to confirm the utility of increased running cadence as a management strategy for running related injuries (Esculier et al, 2016) but current evidence is promising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence suggests that increasing cadence can decrease patello-femoral joint stress (Willson et al, 2014) in people with and without PFPS, however a relationship between this and hip muscle activity or biomechanics has not yet been established. Further work is required to confirm the utility of increased running cadence as a management strategy for running related injuries (Esculier et al, 2016) but current evidence is promising.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge is useful for clinicians and researchers to consider potential targeted rehabilitation strategies for facilitating GMed activity (duration) in this population. We have discussed some potential examples based on recent and proposed work that my ultimately prove effective with further research (Esculier et al, 2016;Willson et al, 2014) The findings of this review also need to be viewed in light of a number of methodological limitations of the included studies. All 13 of the included studies used surface electrodes to analyse the EMG characteristics of GMed in running.…”
Section: Strengths Limitations and Further Researchmentioning
confidence: 99%
“…We hypothesised that all three approaches would be efficient in decreasing symptoms and improving function, but that both the exercises and gait retraining groups would experience greater improvements than the education group, with faster improvements in the gait retraining group secondary to decreased PFJ forces during running. This RCT was registered on ClinicalTrials.gov (NCT02352909) and the study protocol has been published 25…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Others have shown that there are techniques that have been effective in modifying injury risk factors within runners once the risk factors have been identified. 4,5,6,7,8,9 If screening protocols were to be more widely employed to evaluate the risk factors for RRI, it would be important to determine the reliability of raters for such risk factors. Therefore, the purpose of this study was to examine the reliability of an experienced versus and experienced rater in the evaluation of running biomechanics using a 2dimensional running gait analysis.…”
Section: Reliability Of 2-dimensional Running Gait Analysismentioning
confidence: 99%